KODIFIKASI HUKUM PEMILIHAN: INTEGRASI REZIM PEMILU, PILKADA, DAN PILKADES DALAM SISTEM REGULASI UNIFIKATIF - Dian Taufik Ramadhan; Agusli Matondang (Jurnal Ilmu Hukum Kanturuna Wolio, 2026)
The practice of democracy in Indonesia suffers from regulatory fragmentation due to the separation of the electoral regimes for general elections, regional elections, and village elections. This separation has led to overregulation, sectoral self-interest, and gaps in procedural law—particularly in village elections, which are often overlooked in the management of national elections. Consequently, anomalies have emerged, such as a moratorium on village elections due to scheduling conflicts with general elections, protracted disputes in the Firdaus Village case, and horizontal conflicts at the grassroots level. This normative legal study employs legislative, conceptual, case-based, and historical approaches to analyze the urgency of regulatory unification. Through the analytical framework of censorial jurisprudence, the hierarchy of norms, the legal system, and the Volksgeist, the research findings indicate that the consolidation of these three regimes into a single Election Law Code (codification) is an urgent necessity to restore the sovereignty of the people. The reconstruction is designed through an integrative approach to legal pluralism, standardizing electoral justice at the national level, expanding the roles of the General Elections Commission (KPU) and the Elections Supervisory Agency (Bawaslu), and transferring village head election disputes to a specialized electoral tribunal without undermining the villages’ inherent autonomy.